2017
DOI: 10.1016/j.baae.2017.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity effects on ecosystem functioning in a 15-year grassland experiment: Patterns, mechanisms, and open questions

Abstract: In the past two decades, a large number of studies have investigated the relationship between biodiversity and ecosystem functioning, most of which focussed on a limited set of ecosystem variables. The Jena Experiment was set up in 2002 to investigate the effects of plant diversity on element cycling and trophic interactions, using a multi-disciplinary approach. Here, we review the results of 15 years of research in the Jena Experiment, focussing on the effects of manipulating plant species richness and plant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
383
7
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 361 publications
(445 citation statements)
references
References 308 publications
19
383
7
1
Order By: Relevance
“…Moreover, in contrast to many other biodiversity studies, both under experimental (see, e.g., Tilman et al 2014, Weisser et al 2017) and natural conditions (Grace et al 2016, Duffy et al 2017, in our experiment we observed very few or negative relationships between diversity and biomass production. Moreover, in contrast to many other biodiversity studies, both under experimental (see, e.g., Tilman et al 2014, Weisser et al 2017) and natural conditions (Grace et al 2016, Duffy et al 2017, in our experiment we observed very few or negative relationships between diversity and biomass production.…”
Section: August 2018contrasting
confidence: 99%
See 2 more Smart Citations
“…Moreover, in contrast to many other biodiversity studies, both under experimental (see, e.g., Tilman et al 2014, Weisser et al 2017) and natural conditions (Grace et al 2016, Duffy et al 2017, in our experiment we observed very few or negative relationships between diversity and biomass production. Moreover, in contrast to many other biodiversity studies, both under experimental (see, e.g., Tilman et al 2014, Weisser et al 2017) and natural conditions (Grace et al 2016, Duffy et al 2017, in our experiment we observed very few or negative relationships between diversity and biomass production.…”
Section: August 2018contrasting
confidence: 99%
“…F. VEEN ET AL. 8 experiments (e.g., Lehman and Tilman 2000, van Ruijven and Berendse 2005, Tilman et al 2006, Hector et al 2010, Weisser et al 2017 or natural conditions (Duffy et al 2017, Gross et al 2017, we found very few relationships between diversity and ecosystem functioning and the ones we found were generally negative, for both taxonomic and functional diversity. 99,No.…”
contrasting
confidence: 54%
See 1 more Smart Citation
“…Shannon et al 2019), we here provide an example from our own observations that made us aware how gender representation changes along the scientific career. In the Jena Experiment (http://www.the-jena-experiment.de/), a large research consortium studying the ecosystem consequences of biodiversity loss funded by the German Research Foundation (Weisser et al 2017, Eisenhauer et al 2019), we noticed that the percentage of female scientists drops sharply from the level of PhD students (75%) to postdocs (42%) to PIs (35%, a percentage that still is far above the proportion of female professors at many German universities). Please note that these numbers are not supposed to be representative, but just an example.…”
Section: Recommendation 11: Facilitate Gender Equalitymentioning
confidence: 99%
“…A higher microbial diversity is expected to reduce invasion of pathogens and increase antagonism in soils, thereby reducing the impact of plant pathogenic fungi (Larkin 2015;Mallon et al 2015). In fact, an increase in plant diversity in the Jena biodiversity experiment (Weisser et al 2017) enhanced the activity of antagonistic bacteria in the soil against the soil-borne fungal pathogen R. solani (Latz et al 2012). Also in natural grasslands, the diversity of neighbouring plants has been found to affect Streptomyces spp.…”
Section: Indirect Neighbour Effects Via the Root Microbiomementioning
confidence: 99%